PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA MATERI TUMBUHAN SUMBER KEHIDUPAN MELALUI MODEL PEMBELAJARAN PBL - Mochajati; Endang Suprapti; Umi Arsiyati (PROCEEDING UMSURABAYA, 2024)
This research was conducted at SD Wali Idris, Tambaksari District, Surabaya City, with the subjects being fourth-grade students. The total number of students was 16, consisting of 10 boys and 6 girls. The object of the research was the teaching of Natural Science with the topic "Plants as a Source of Life. " The method used was the Problem-Based Learning (PBL) approach. The research process was carried out in three cycles, each consisting of four stages: planning, implementation, observation, and analysis and reflection. The results of this study indicate that the Problem-Based Learning (PBL) method is effective for teaching Natural Science on the topic "Plants as a Source of Life" to fourth-grade students.